SIMBOL DAN IRONI DALAM CERPEN THE LOTTERY, KARYA SHIRLEY JACKSON - Syam, Essy (Jurnal Ilmu Budaya, 2012)
A work, particularly literary work consists of many interesting elements to analyze. It's true for I have .figured out that "The Lottery" written by Shirley Jackson, is a rich work so that I can explore about many things from this work In this case, particularly I focus on analyzing the work dealing with symbols and ironies. The most ironic element found is the ritual lottery itself Genereally, most people who get lottery are lucky because they usually get gift or other lucky thing. Ironically, in this story, the person who gets the lottery is stoned to death.